A survey on stability and rigidity results for Lie algebras - Crainic, Marius; Schätz, Florian; Struchiner, Ivan (Indagationes mathematicae, 2014)
We give simple and unified proofs of the known stability and rigidity results for Lie algebras, Lie subalgebras and Lie algebra homomorphisms. Moreover, we investigate when a Lie algebra homomorphism is stable under all automorphisms of the codomain (including outer automorphisms).